The Development of a Moisture-Stressed Tree-Ring Chronology Network for the Southern Canadian Cordillera - Watson, Emma (Tree-Ring Society, 2001)
Fifty-three ring-width chronologies have been developed from open-grown, low-elevation stands of Pseudotsuga menziesii (Douglas-fir) and Pinar ponderosa (ponderosa pine) in the southern Canadian Cordillera. These chronologies will be used to develop precipitation reconstructions for the region. The sites are unevenly distributed across the interior valleys from east of the Coast Ranges to the Canadian Rockies and from the Canada-U.S. border to the northern limits of both species. The chronologies range from 123-691 years (mean = 383 years) and, on average, have a strong within-chronology common signal (Expressed Population Signal > 0.85) with as few as eight trees. A Rotated Principal Components Analysis (RPCA) identified three regions within which annual ring-width chronologies covary similarly. A preliminary assessment of regional chronologies and patterns of extreme narrow and wide marker rings demonstrates that common growth variations exist in the chronology network that are probably precipitation related. Both the RPCA and marker ring analyses suggest distinctive regional patterns of growth on both interannual and longer timescales that vary through time and are possibly linked to persistent large scale climatic anomalies.